The Nature and Constitutionality of Stalking Laws - Guy, Jr (1993)
In 1989, an obsessed fan shot and killed actress Rebecca Schaeffer at the front gate of her Los Angeles apartment.' Soon thereafter, in unrelated incidents, five Orange County women were slain at the hands of their intimate partners. All of the killings shared two common attributes: the killers had stalked their victims incessantly, and the justice system had been unable to intervene. Suddenly conscious of the inadequacy of current law, the California legislature responded in 1990 by creating the nation's first stalking law. The statute criminalizes the repeated harassment or following of an- other person in conjunction with a threat. California is enforcing the law aggressively.' Thirty states have followed California's move and enacted stalking laws.' The brutal killing of at least one woman in each state usually has prompted the passage of these laws. Many of the statutes are identical to the California law, but a few differ substantially in both scope and language. Some target repeated harassment; others target only literal stalking, such as following and surveillance. Some require a threat, others only conduct.' Further differences abound. No stalking statute has faced a constitutional challenge at the appellate level.' Yet, since their inception, the statutes have been the source of much controversy. Civil libertarians claim that stalking laws contravene the Constitution by making criminal and innocent behavior indistinguishable and by infringing on First Amendment rights. Others criticize the statutes as a politically safe shortcut that legislators have adopted to address a pervasive crisis too complex for a single law. In October 1992, Congress recognized the need for comprehensive stalking legislation that will pass constitutional muster, and it enacted a law charging the National Institute of Justice with the duty of drafting a model stalking law.' The Institute has one year from the law's enactment to research and develop the model law, which will serve as a guide for states wishing to enact stalking legislation or to solidify their current stalking laws.' Meanwhile, states continue to enact and enforce their own stalking laws. This Note will analyze the language and scope of stalking laws and various aspects of their constitutionality. Part II discusses the nature of stalking behavior and the past failures of the legal system to address it adequately. Part III analyzes stalking laws that various states have enacted, focusing on the California, Florida, and Connecticut statutes as representative examples. In Part IV, this Note addresses potential constitutional challenges to stalking statutes. First, it analyzes whether the statutes violate substantive due process by creating criminal liability before the stalker has demonstrated culpability. It concludes that the statutes are constitutional under this aspect of substantive due process. Second, it addresses the constitutionality of stalking laws under the void for vagueness doctrine, concluding that some stalking statutes are unconstitutionally vague while others survive vagueness scrutiny. Part V proposes a model stalking statute that circumvents many of the vagueness problems present in current stalking laws. This Note concludes in Part VI with a call for states to enact comprehensive, effective stalking laws that meet constitutional requirements